DAMPAK MERGER TERHADAP KINERJA KEUANGAN (STUDI KASUS PADA PERUSAHAAN TERDAFTAR BEI 2018-2021) - Narulita, Sari (Fakultas Ekonomi, 2023)
This research aims to find out whether the company's financial ratio after a merger has changed or not. This study uses the company's financial statements, which are the ratio of financials to the observation year 2 years before and 2 years after the merger. This research was conducted to test financial performance measured by financial ratios, namely Current Ratio (CR), Net Proft Margin (NPM), Debt to Equity Ratio (DER), Return On Equity (ROE).This research used all companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2021. The research was conducted by quantitative method and sampling in the study using purposive sampling is known as many as 10 companies registered in IDX period 2018-2021 according to the specified criteria. The analysis used to test the hypothesis of this study is to use a non parametric statistic test, using the data normality test (Shapiro Wilk) Wilcoxon Signed rank Test and Paired sample t-Test. Results from the study showed that tests of current ratio, Net Profit Margin, Return On equity, Debt to Equity Ratio showed no significant differences before and after the merger